Edukasi Kesehatan Lingkungan Kepada ABK dan Inspeksi Sanitasi Kapal Quantum One di Pelabuhan Tenau Kupang - Diniati Diniati; Evy Linda Tata; Karolina T. Bokilia; Kiki S. Lulu; Yuli F. Mansula; Marylin S. Junias; Luh Putu Ruliati; Anderias Umbu Roga (Universitas Pahlawan Tuanku Tambusai, 2026)
Ships are work environments with relatively high environmental health risk due to engine noise exposure, the need to maintain woom sanitation, and the monitoring of clean water quality to prevent health problem among crew members. This community service activity aimed to increase the knowledge and awareness of ship crew members regarding environmental health and noise control on the Quantum One ship operating at Tenau Port, Kupang. The activity method included ship sanitation inspection, participant registration, a pre-test, blood pressure measurement, health education on environmental sanitation and noise hazards through short presentation and leaflet distribution, a post-test, handwadhing demonstration, installation of educational posters and stickers, and demonstration of water pH and engine-room noise measurements. The results showed and increase in participant knowledge, with the mean pre-test score rising from 86,52 to 97,57 in the post-test. The ship’s sanitation condition was generally good, the clea water pH value was 7,9 which remained within a safe range, and the measured noise level was 83 dBA, still below the threshold limit of 85 dBA/8 working hours. In conclusion, environmental health education and ship sanitation inspection effectively improved the crew members’ knowledge and supported the implementation of clean and healthy living behaviors on board. It was recommended that education, sanitation, and noise control be carried out regularly and continuously on the ship.